Profil Resiliensi Akademik Berdasarkan Jenis Kelamin pada Mahasiswa yang Menyusun Skripsi - Oktavianti, Aldini; Dartina, Vina; Rachmaniar, Ananda (Ma'soem University, 2024)
There are many unpleasant situations when writing a paper, so students need to have academic resilience. Students who have good academic resilience will be able to struggle so that when faced with difficulties or pressure in an academic setting they will not give up easily, academic resilience will change students' thinking styles and the level of academic success. Resilient students will be able to overcome difficulties experienced, rise from the pressure they face, be able to manage stress, emotions that arise as a result of situations that occur. The research that was conducted had the aim of measuring the resilience of academic students who were compiling paper at Ma'soem University based on gender. Measuring student academic resilience is considered important because it will be able to measure a student's ability to deal with pressure in an academic setting. This study uses a quantitative method with a descriptive and survey approach. The number of sampling is 122 person. Analysis of the data used to find out the profile is the three categorization formula and testing the difference using the t-test formula. The results of the study revealed that in general the condition of student academic resilience was in the high category and there was no difference in the level of academic resilience between students and female students.